External Perceptions and EU Foreign Policy Effectiveness: The Case of Climate Change1. (11th April 2014) - Torney, Diarmuid
Abstract Recent research on external perceptions of the European Union (EU) has not explored sufficiently the implications of its findings for the effectiveness of EU external policies. To address this gap, this article explores the relationship between external perceptions and effectiveness by considering the case of climate change in which, despite broadly favourable external perceptions, EU external effectiveness has been somewhat limited. It uses the case of Chinese and Indian relations with the EU on climate change to illustrate that the findings of the external perceptions literature should be interpreted in the light of the dynamics of specific policy areas as well as broader changes in the context of world politics. The argument is illustrated using the example of negotiations on the continuation of the Kyoto Protocol beyond 2012, which shows how, under certain circumstances, positive external perceptions may in fact limit external effectiveness.